A partitioned solution approach for the simulation of dynamic behaviour and acoustic signature of flexible cavitating marine propellers. (1st February 2020) - Lampe, Tobias; Radtke, Lars; Abdel-Maksoud, Moustafa; Düster, Alexander
Abstract: Upcoming legislative developments and modern propeller designs call for numerical methods which are able to assess the complex interaction of the propeller's hydrodynamic and structural dynamic behaviour as well as the resulting influence on the acoustic signature. In this work, the problem is engaged making use of a partitioned, strongly coupled solution approach, thus enabling the usage of specialized solvers for each domain. On the fluid side, a boundary-element-method is applied while on the structural side a finite element method is employed. Information transfer between each subproblem is handled by a separate coupling tool. The acoustic evaluation is performed by means of a Ffowcs Williams-Hawkings equation based technique. In the present paper, the main focus is to establish the method's capability to simulate the interaction of all fields and its' physical consistency. The results show that an external excitation of the blade can be captured in the resulting acoustic spectrum. Highlights: Partitioned solution approaches are efficient for fluid-structure-interaction problems. Ffowcs Williams-Hawkings Equation is highly favourable for boundary-element-methods. Structural vibrations can be captured by the presented approaches. Structural vibrations can affect the acoustic signature of propellers for non-cavitating cases.